Speechway and U-Dictionary : Applications for Speaking Anxiety Reduction - Nadzifah, Wardatun; Dwi Fita Heriyawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Speaking is one of the most challenging skills in learning foreign language. Several affective factors such as shame and fear of making mistakes and being laughed by others lead students to have anxiety in uttering foreign language. The role of digital media, especially smartphone that becomes a “close friend“ of mostly students nowadays is utilized as a media to reduce students’ speaking anxiety. This study aimed to investigate the use of Speechway and U-Dictionary application in reducing students’ speaking anxiety. FLSAS was used to measure students’s speaking anxiety level. The results showed that Hafshawaty University students’ speaking anxiety level were mostly in the level of moderate anxiety. Some were in high anxiety and a few of them were in low anxiety. The use of Speechway and U-Dictionary application significantly contributed to alleviate the students’ speaking anxiety that produced 0% of high anxiety level and low anxiety category encountered a 48.94% increase. However there are still 14.89% students were still in moderate anxiety level in the end of this study. Indeed, the Speechway and U-Dictionary helped students overcome their speaking anxiety. Keywords: speechway; speaking anxiety; u-dictionary